Extending Public Water Supply in Peri-Urban Area: Technical-Engineering, Economic, and Environmental Consideration. (2015) - Maryati, Sri; Humaira, An Nisaa' Siti
Abstract: Peri-urban is a gray area between urban and rural areas. The big differences between the urban and rural areas are still not able to explain the circumstances and conditions required by people who live in the peri-urban areas, including the needs for infrastructure provision, particularly public water supply. The needs for the provision of clean water in peri-urban areas basically do not have any different from those communities in urban areas, yet the conditions are not as good as clean water infrastructure service in urban areas. PDAMs ( Perusahaan Daerah Air Minum ) in BMA (Bandung Metropolitan Area) as a local water enterprise only serves 8.91% of households living in peri-urban areas, while 48.24% of population in the urban areas has been already served by PDAM itself. An effort to extend public water services in peri-urban area faces a number of problems including technical-engineering, economic, and environmental issues. The purpose of this paper is to outline the technical-engineering, economic, and environmental issues in the expansion of public water services in peri-urban areas. The case study in this research is Bandung Metropolitan Area. Data used consist of secondary data. Technical-engineering aspect was analyzed through population density approach and economic aspect was analyzed by the means of willingness and ability to pay approach, while the environmental aspect was analyzed through the use of water resources at this time. The results showed that in terms of technical-engineering aspect and willingness to pay, it is not feasible to develop a public system, but in terms of ability to pay and environmental aspect, it is possible to develop public system. It is proposed to develop communal system to serve residents in densely populated cluster with proper tariff system. It is also recommended to control the individual water use.